Children in left-behind migrant households: Education and gender equality - Sundus Saleemi (University of Bonn, Center for Development Research (ZEF), 2021)
This paper analyses the effect of migration of men from rural areas in Pakistan on children in households "left behind" by the migrants. Left-behind households' expenditure on children's education and the gendered distribution of these expenditures are two outcomes of main interest. First, it is tested if left-behind households have higher overall expenditures on children's education. Second, it is tested if migration of men from households reduces gender inequality in households' expenditures on children's education. This gendered distribution is analyzed by estimating the effect of migration on the share of households' education expenditures spent on girls. Migration can affect these expenditures and its gendered distribution through various channels. Men's migration may lead to women taking over household decisions regarding education expenditures. Migration may also transfer norms and alter peoples' preferences such as those regarding children's schooling. To differentiate between the channels two types of migration, permanent migration of men for employment creating "left-behind" households and temporary migration whereby male members migrate for employment for short periods during the year, have been considered. Transfer of norms is expected to operate through temporary migration episodes as well as via permanent migration, while the changes in women's decision making is expected to operate via permanent migration when the men are absent. The effect of remittances has been further separated from the effect of migration. The paper uses longitudinal data from rural households in Pakistan with additional data collected from a sub-sample of the panel by the author. Fixed effects fixed effects model (FEM) is used to estimate these relationships, reducing endogeneity of migration. The results suggest that migrant and non-migrant households in the sample do not have significantly different expenditures on children's schooling and education. This is true for both types of migration. Households that receive remittances have higher expenditures on children's education. A noteworthy result is that left-behind households have girls' shares that are higher as much as 18 percent than the average. This is not the case for households with temporary migrants, suggesting that women's decision participation decreases gender inequality in households' education expenditures. Heckman Selection Model has additionally been estimated to estimate the effect of the migration on households' expenditure on girls' education, considering the selection of households into sending girls to school. Heckman Selection model also suggests that left-behind households have higher per girl expenditures. The results of the selection model suggest that being a left-behind household is significantly positively associated with households' expenditures on girls' education.
Keywords: O15; D15; J16; F22; 330; migration; women's empowerment; intra-household resource allocation